A clinico-epidemiological analysis of subclinical hypothyroidism in a tertiary care health center - Agrawal, Vaibhav; Patil, Virendra; Kshirsagar, Ashok (International Journal of Advances in Medicine, 2019)
Background: Subclinical hypothyroidism (SCH) is defined by increase in serum thyroid stimulating hormone (TSH) and free thyroxine (FT4) and free triiodothyronine (FT3) levels within normal range, coupled with absence of typical clinical symptoms. The present study was undertaken to analyse the SCH associated comorbidities, especially lipid disturbances, thyroid autoantibodies, etc. Methods: The present study was retrospective observational study, which was carried out at a tertiary health care center. Results: Out of the 100 patients, majority were in the age group 21 to 30 years (31 patients), followed by 26 patients in age group >51 years and least in age group 41 to 50 years. Prevalence showed female predilection, with female: male ratio of 1.9:1. Most common symptom reported was general fatigue, which was encountered in 40 patients, followed by weight gain, menstrual abnormalities, and constipation. 10 patients were asymptomatic. Serum TSH range in the patients was 5 to 21.1 µIU/l, while mean TSH was 10.9 µIU/l. 20 patients were found to have serum TSH>10. Conclusions: Despite high prevalence, detection rate of subclinical hypothyroidism is very low. Carrying out epidemiological study on national scale is need of the hour, as lack of typical clinical features makes the detection less likely and it has numerous complications, if untreated.